Beekeeping - Paterson, Peter D. (Technical Centre for Agricultural and Rural Cooperation, 2006)
Through its clear explanatory text and admirable illustration this book skilfully lays out the elements of good practice in tropical bee-keeping. It explains both traditional techniques using low-cost hives and more advanced methods, pointing out the most appropriate system for the level of investment the bee-keeper wishes to make. The author has a wealth of knowledge, developed through years of thoughtful observation and practical experiences working with bee-keepers all over Africa and with his own hives in Kenya. Existing bee-keepers wishing to improve their techniques and those looking to start a new bee-keeping enterprise will find the book invaluable.